Hide and seek: interplay between influenza viruses and B cells - Kuraoka, Masayuki; Adachi, Yu; Takahashi, Yoshimasa (International immunology, 2020)
Abstract Influenza virus constantly acquires genetic mutations/reassortment in the major surface protein, hemagglutinin (HA), resulting in the generation of strains with antigenic variations. There are, however, HA epitopes that are conserved across influenza viruses and are targeted by broadly protective antibodies. A goal for the next-generation influenza vaccines is to stimulate B-cell responses against such conserved epitopes in order to provide broad protection against divergent influenza viruses. Broadly protective B cells, however, are not easily activated by HA antigens with native structure, because the virus has multiple strategies to escape from the humoral immune responses directed to the conserved epitopes. One such strategy is to hide the conserved epitopes from the B-cell surveillance by steric hindrance. Technical advancement in the analysis of the human B-cell antigen receptor (BCR) repertoire has dissected the BCRs to HA epitopes that are hidden in the native structure but are targeted by broadly protective antibodies. We describe here the characterization and function of broadly protective antibodies and strategies that enable B cells to seek these hidden epitopes, with potential implications for the development of universal influenza vaccines.